Reliability and reproducibility of antinuclear antibody testing in pediatric rheumatology practice - Ostrov, Barbara E. (Frontiers in Medicine, 2023)
Antinuclear antibody (ANA) testing is common practice among health care practitioners when evaluating children and adolescents with non-specific symptoms including fatigue and aches and pains. When positive, ANA results often lead to referrals to pediatric rheumatologists as these antibodies may be key indicators for specific pediatric rheumatologic diagnoses. The reliability and reproducibility of ANA tests varies with assay techniques and validation and interpretation of results. In the following article, review of ANA testing in pediatrics is provided along with case examples that demonstrate the reliability and reproducibility of these results in specific scenarios common in the practice of pediatric rheumatology. Guidelines for more accurate utilization of ANA testing are presented with the aim to improve testing and interpretation by ordering clinicians.